Immediate Effects of the Initial FDA Notification on the Use of Surgical Mesh for Pelvic Organ Prolapse Surgery in Medicare Beneficiaries - Reynolds, W. Stuart (2012)
AIMS: Prompted by increased reports of complications with the use of mesh for pelvic organ prolapse (POP) surgery, the FDA issued an initial public health notification (PHN) in 2008. We proposed to determine if the numbers of POP cases augmented with surgical mesh performed in U.S. Medicare beneficiaries changed relative to this PHN. METHODS: Using administrative healthcare claims for beneficiaries enrolled in the U.S. Medicare program from 2008 to 2009, we identified women who underwent POP surgery with and without surgical mesh by procedural and diagnosis coding. In addition to comparing cases with and without mesh, we also calculated rates (number of cases per 100,000 female beneficiaries) and compared these relative to the timing of the PHN. RESULTS: We identified 104,185 POP procedures, of which 27,839 (26.7%) included mesh material and 76,346 (73.3%) did not. Between the last three quarters of 2008 and the first three of 2009, the rates of mesh cases increased (40.3–42.1, P < 0.001) and those without mesh decreased (115.5–111.4, P < 0.001). Inpatient procedures decreased and outpatient procedures increased for both those with and without mesh augmentation. For inpatient procedures, the relative use of biologic graft and synthetic mesh material did not vary over the study period. CONCLUSIONS: A substantial number of Medicare beneficiaries underwent mesh POP procedures in 2008–2009. However, despite the PHN cautioning about potential mesh complications, the numbers of mesh cases continued to rise in the immediate period after the PHN.